Chińskie "otwarcia" na wpływy gospodarki światowej - Muszkiewicz, Marian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
China is a huge country with a history of almost three thousand years and with a culture as old. After two hundred years of weakness, this systematically, now, developing country is aiming at the regaining of its lost power, striving after the participation in the functioning of the contemporary world adequate for the country inhabited by one fourth of the population of the globe. Due to the growing globalisation of the contemporary world, the aspect of China's functioning and its aspirations to become, in the future, the first superpower of the globe, seems vital and worth considering. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 135-152